95.0k views
5 votes
How to solve that question? ​

How to solve that question? ​-example-1
User Jacobko
by
5.3k points

1 Answer

2 votes

Answer:

(i) (x√x)/3 -(√x)/2

(ii) f(x) = x³/27 +3x -5

Explanation:

You want the value of the integral in each case. One integral is indefinite, the other has conditions specified.

In each case, the power rule applies:


\displaystyle \int{x^n}\,dx=(x^(n+1))/(n+1)

(i) indefinite integral

The integral can be rewritten as the sum of two integrals involving half powers.


\displaystyle \int{(2x-1)/(4√(x))}\,dx=(1)/(2)\int{x^{(1)/(2)}}\,dx-(1)/(4)\int{x^{-(1)/(2)}}\,dx=\frac{x^{(3)/(2)}}{2\left((3)/(2)\right)}-\frac{x^{(1)/(2)}}{4\left((1)/(2)\right)}\\\\=\boxed{(1)/(3)x√(x)-(1)/(2)√(x)}

(ii) f'(x)=ax²+b

You are given the derivative and three conditions:

  • f'(x) = ax² +b
  • f'(3) = 4
  • f(3) = 5
  • f(0) = -5

Together with the integral, the conditions give rise to three equations in the three unknown coefficients.


\displaystyle f(x) = \int{ax^2+b}\,dx=(a)/(3)x^3+bx+c

Then the equations we can write for a, b, c are ...

f'(3) = 4 ⇒ a(3²) +b = 4

f(3) = 5 ⇒ (a/3)(3³) +b(3) +c = 5

f(0) = -5 ⇒ a(0³) +b(0) +c = -5

The last equation gives the value of c = -5, so the remaining equations become ...

9a +b = 4

9a +3b = 10

Subtracting the first from the second, we have ...

(9a +3b) -(9a +b) = (10) -(4)

2b = 6

b = 3

Using this in the first equation, we find 'a' to be ...

9a +3 = 4

a = 1/9

Then f(x) is ...


\boxed{f(x)=(1)/(27)x^3+3x-5}

User Darnell
by
5.6k points